PSII-30 The genetics of functional teats in swine. (5th December 2019) - Earnhardt, Audrey L; Knauer, Mark
Abstract: The objective of this study was to evaluate the genetics of functional teats in swine. Piglet survival is of great importance for swine producers throughout the world due to its relationship with animal well-being and farm profitability. Availability and accessibility of functional teats on a sow during lactation is essential for enhancing piglet livability. Teat traits including total teat number (TT), functional teat number (FT), and non-functional teat number (NFT), were observed and recorded on 3, 249 Landrace × Large White F1 sows. Damaged teat number (DT) and functional mammary gland number (FG) were also observed on sows prior to weaning. Variance components were estimated using AIREMLF90, with parity and farm as fixed effects. Means for TT, FT and NFT at farrowing were 14.94, 13.91 and 1.03, respectively, and 14.43, 13.02 and 1.15, respectively at weaning. Means for TT and FT were greater (P < 0.01) at farrowing than at weaning. Heritability estimates for TT, FT and NFT ranged between 0.19 and 0.30, 0.17 and 0.24, and 0.12 and 0.16, respectively. Total teat number and functional teat number had positive genetic correlation estimates ranging from 0.74 to 0.77. Functional mammary glands had a negative linear relationship of -1.16 with DT, and genetic correlations of 0.87 and -0.83 with FT and NFT, respectively. Linear regression models relating TT and FT to number of piglets weaned revealed that an increase of one functional teat at farrowing increased number weaned by 0.26. Overall, there was sufficient genetic variation for total teat number and functional teat number signifying that genetic gains from selecting for these traits is possible. Results also suggest that by focusing selection on functional teat number, an increase in non-functional teat number can be avoided. Therefore, utilizing functional teat number in the breeding goal should improve the general teat quality and sow performance.